The dramaturg's gaze as a gateway to relevant, responsive, and relational pedagogical practice - Rose Martin (Cappelen Damm Akademisk NOASP, 2021)
Book review: Østern, A.-L. & Knudsen, K. N. (Eds.). (2021). Teaching and learning through dramaturgy: Education as an artful engagement. Routledge. 156 pages. ISBN: 9780367549084.